Mitos Alam dan Nilai Pendidikan dalam Cerita Rakyat Asal Mula Mafu Gayoba Karya Ryan M. Khamary - Madi, Nasrullah La; Adriani, Adriani; Muhamad, Darlisa; Yusrina, Yusrina (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
The purpose of the research is to find out the Natural Myths and Educational Values in the Folklore of the Origin of Mafu Gayoba by Ryan M. Khamary. The method in this study is a qualitative descriptive method. The data in this study are text and dialogue quotes that contain natural myths and educational values. The source of data in this study is the Folklore of the Origin of Mafu Gayoba by Ryan M. Khamary, Based on the analysis of data and conclusions, it can be known that (1) Natural Myths in the Folklore of the Origin of Mafu Gayoba by Ryan M. Khamary are divided into 2, namely spritism and hierophone. The collection technique uses the technique of reading, reading and taking notes, then the data analysis technique, namely. Data reduction, data presentation, conclusion drawing and verification. The results of the research found natural myths and educational values in the folklore The Origin of Mafu Gayoba by Ryan M. Khamary. Natural myths are found to be the natural myths of spritis, and the myths of the hierophone nature while the value of education is found to be moral values, religious values, cultural values, and social values. The classification of data on the myth of the nature of spritism has 8 citations, hierophany 8 citations, as well as educational values, moral values 12 citations, religious values 9 citations, cultural values 7 citations, and social values 8 citations